Tangshen formula attenuates diabetic renal injuries by upregulating autophagy via inhibition of PLZF expression - Zhao, Hailing (PLoS One, 2017)
The Chinese herbal granule Tangshen Formula (TSF) has been proven to decrease proteinuria and improve estimated glomerular filtration rate (eGFR) in diabetic kidney disease (DKD) patients. However, the underlying mechanism of TSF on treatment of diabetic nephropathy (DN) remains unclear. The present study aimed to identify the therapeutic target of TSF in diabetic renal injuries through microarray-based gene expression profiling and establish its underlying mechanism. TSF treatment significantly attenuated diabetic renal injuries by inhibiting urinary excretion of albumin and renal histological injuries in diabetic (db/db) mice. We found that PLZF might be the molecular target of TSF in DN. In vivo, the db/db mice showed a significant increase in renal protein expression of PLZF and collagen III, and decrease in renal autophagy levels (downregulated LC3 II and upregulated p62/SQSTM1) compared to db/m mice. The application of TSF resulted in the downregulation of PLZF and collagen III and upregulation of autophagy level in the kidneys of db/db mice. In vitro, TSF reduced high glucose (HG)-induced cell proliferation for NRK52E cells. Further studies indicated that the exposure of NRK52E cells to high levels of glucose resulted in the downregulation of cellular autophagy and upregulation of collagen III protein, which was reversed by TSF treatment by decreasing PLZF expression. In conclusion, TSF might have induced cellular autophagy by inhibiting PLZF expression, which in turn resulted in an increase in autophagic degradation of collagen III that attenuated diabetic renal injuries.